Penerapan Algoritma Insertion Sort Pada Aplikasi Manajemen Aset E-Asset Fakultas Universitas Islam Sumatera Utara - Muhammad Reza; Khairuddin Nasution; Mhd Zulfansyuri Siambaton (LPPM Universitas Deli Sumatera, 2021)
The asset reporting and processing system at the Faculty of Engineering, Islamic University of North Sumatra still uses a manual system, namely by using the Microsoft Excel application, this is not efficient in the reporting and control process of fixed assets belonging to the Faculty of Engineering, Islamic University of North Sumatra. This E-Asset Asset Management System was created using the PHP programming language for interface design and MySQL for database management. Data processing in this system includes master data consisting of supplier data, location data, category data, goods data, asset data, user data and asset transaction data consisting of procurement of goods and placement of goods that can be added, changed and deleted. In addition, asset data can be sorted using the insertion sort sorting algorithm. In addition, reporting data is also displayed which can be viewed directly in the system or printed. Keywords: E-Asset; Asset Management; Insertion Sort; Sorting Algorithm.